2013
DOI: 10.4161/adip.24752
|View full text |Cite
|
Sign up to set email alerts
|

Rats perinatally exposed to food restriction and high-fat diet show differences in adipose tissue gene expression under chronic caloric restriction

Abstract: The aim of this study is to analyze how maternal diet during the lactational period influences the adipose tissue response to chronic caloric restriction in offspring. Lactating dams were subjected to one of three treatments: 50% food restriction (FR), ad lib standard chow (AL), or ad lib high-fat diet (HF). Juveniles were first weaned onto standard chow, then in adulthood 50% calorically restricted and maintained at 90% of normal body weight for 60 d. HF animals showed increased percent body fat compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…Previous studies by us and others have demonstrated that adipose tissue is very vulnerable to the effects of developmental programming and is the site in which some of the earliest and most striking programming effects are observed (15, 30, 31). Consistent with these observations, in the current study, we have shown a reduction in IRS-1 and p110- β insulin signaling protein expression in response to suboptimal nutrition in utero and catch-up growth.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies by us and others have demonstrated that adipose tissue is very vulnerable to the effects of developmental programming and is the site in which some of the earliest and most striking programming effects are observed (15, 30, 31). Consistent with these observations, in the current study, we have shown a reduction in IRS-1 and p110- β insulin signaling protein expression in response to suboptimal nutrition in utero and catch-up growth.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, animal studies have indicated the potential for BM to promote the transfer of obesity from mother to offspring ( Del Prado, Delgado & Villalpando, 1997 ; Mackay et al, 2013 ; Matsuno et al, 1999 ; Oosting et al, 2015 ; Palou et al, 2010 ; Sun et al, 2012 ; Tsuduki et al, 2013 ). The influence of factors within the BM, which could contribute to the maternal transfer of obesity, have rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue is a major contributor to whole body insulin sensitivity 40 and this tissue is particularly vulnerable to the effects of developmental programming 12 , 41 , 42 . Although para-ovarian fat pad mass was increased in F2 recuperated animals, no effect of grand-maternal diet upon adipocyte cell size was observed.…”
Section: Discussionmentioning
confidence: 99%